Response of Various Mycorrhizal Inoculants on Rice Growth, Productivity and Nutrient Uptake - Poddar, Ratneswar; Sen, Arup; Kundu, R.; Das, Himangshu; Bandopadhyay, P. (International Journal of Bio-resource and Stress Management, 2020)
Mycorrhizal inoculant is one of the options to increase the nutrient availability in soil which ultimately increases the crop yield. The effect of various mycorrhizal inoculants on plant growth and nutrient status in Kharif rice was studied at ‘C’ block farm of Bidhan Chandra Krishi Viswavidyalaya, Kalyani, West Bengal, India. The soil was was typical Gangetic Alluvium with sandy loam in texture with medium water holding capacity. The experiment comprises of nine treatments replicated thrice in RBD during 2016 and 2017. The crop having treated with RhizoMyco @ 250 g ha-1 at 15 DAT significantly increased plant height, dry matter accumulation (DMA), leaf area index (LAI), crop growth rate (CGR), yield attributes and yield than others. The range of increase was 0.72% to 27.17% in grain yield under mycorrhizal inoculants treatments over untreated control in this experiment. Grain yield was maximum (3.51 t ha-1) in the treatment applied with RhizoMyco @ 250 g ha-1 at 15 DAT which was statistically superior over other treatments except T5. Nutrient availability in soil and uptake of N, P and K was also found higher in RhizoMyco application. A positive correlation prevailed in between different growth and yield parameter of rice with available N, P, K in soil and uptake of different nutrients by plant. This study suggests growing transplanted rice with application of RhizoMyco @ 250 g ha-1 at 15 DAT for better growth, higher productivity and higher nutrient uptake.